2018
DOI: 10.1371/journal.pone.0191219
|View full text |Cite
|
Sign up to set email alerts
|

An ancestral TMEM16 homolog from Dictyostelium discoideum forms a scramblase

Abstract: TMEM16 proteins are a recently identified protein family comprising Ca2+-activated Cl- channels that generate outwardly rectifying ionic currents in response to intracellular Ca2+ elevations. Some TMEM16 family members, such as TMEM16F/ANO6 are also essential for Ca2+-dependent phospholipid scrambling. TMEM16-like genes are present in the genomes of most eukaryotic species, the function(s) of TMEM16 family members from evolutionary ancient eukaryotes is not completely clear. Here, we provide insight into the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Mammalian TMEM16A and TMEM16B are Ca 2+ -activated Cl - channels (Schroeder et al, 2008; Caputo et al, 2008; Yang et al, 2008; Stephan et al, 2009), while other members with phospholipid scrambling functions display modest cation-selective or non-selective ion channel activities, such as TMEM16E (Whitlock et al, 2018), TMEM16F (Yang et al, 2012; Alvadia et al, 2019; Yu et al, 2015; Le et al, 2019a), Drosophila subdued (Le et al, 2019b), and two fungal TMEM16 homologs (Malvezzi et al, 2013; Brunner et al, 2014; Lee et al, 2016; Jiang et al, 2017). The lipid scrambling activity is also observed in an amoebozoa TMEM16 homolog (Pelz et al, 2018). All the TMEM16 proteins, based on reported structures and sequence alignment, are dimers with each monomer containing 10 transmembrane helices with conserved Ca 2+ -binding sites (Alvadia et al, 2019; Brunner et al, 2014; Paulino et al, 2017a; Bushell, 2018; Dang et al, 2017; Feng et al, 2019; Kalienkova et al, 2019; Falzone et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Mammalian TMEM16A and TMEM16B are Ca 2+ -activated Cl - channels (Schroeder et al, 2008; Caputo et al, 2008; Yang et al, 2008; Stephan et al, 2009), while other members with phospholipid scrambling functions display modest cation-selective or non-selective ion channel activities, such as TMEM16E (Whitlock et al, 2018), TMEM16F (Yang et al, 2012; Alvadia et al, 2019; Yu et al, 2015; Le et al, 2019a), Drosophila subdued (Le et al, 2019b), and two fungal TMEM16 homologs (Malvezzi et al, 2013; Brunner et al, 2014; Lee et al, 2016; Jiang et al, 2017). The lipid scrambling activity is also observed in an amoebozoa TMEM16 homolog (Pelz et al, 2018). All the TMEM16 proteins, based on reported structures and sequence alignment, are dimers with each monomer containing 10 transmembrane helices with conserved Ca 2+ -binding sites (Alvadia et al, 2019; Brunner et al, 2014; Paulino et al, 2017a; Bushell, 2018; Dang et al, 2017; Feng et al, 2019; Kalienkova et al, 2019; Falzone et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…However, it is now recognized that many ANO paralogs are not Cl − channels but have other functions, most notably Ca 2+ -activated phospholipid scrambling (Ca 2+ -PLS; Suzuki et al, 2010; Malvezzi et al, 2013; Brunner et al, 2014; Whitlock and Hartzell, 2017). ANO6 was the first ANO found to exhibit phospholipid scramblase (PLSase) activity, but more recently, two ANO homologues from fungi were found to be PLSases when purified and reconstituted into liposomes (Malvezzi et al, 2013; Brunner et al, 2014; Pelz et al, 2018). One of these scramblases has been crystallized (Brunner et al, 2014), which has greatly informed efforts to elucidate how it functions (Bethel and Grabe, 2016; Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The groundbreaking discoveries of TMEM16A 3 and TMEM16B as the long-sought CaCCs (1-3) revealed a novel membrane protein superfamily that includes the TMEM16 family and its closely related OSCA, TMEM63, and TMC membrane protein families (4,5). TMEM16 proteins have been found in fungi (6,7), amoeboids (8), insects (9), and vertebrates (10 -12). The unexpected findings of mammalian TMEM16F as a moonlight-ing protein (13,14), a special type of protein that can perform two or more distinct functions without gene fusions, multiple RNA splice variants, or multiple proteolytic fragments (15)(16)(17)(18), advanced our understanding of the enigmatic TMEM16 family (10 -12, 19, 20).…”
mentioning
confidence: 99%
“…Recent structural and functional studies elegantly revealed that the fungal nhTMEM16, afTMEM16, and mammalian TMEM16E (6,7,12,(23)(24)(25) are also moonlighting proteins with CaPLSase and channel activities. Interestingly, the mammalian TMEM16A and TMEM16B CaCCs only displayed ion channel activities (13,26), whereas an amoebozoa TMEM16 homolog from Dictyostelium discoideum only showed CaPLSase activity when heterologously expressed in HEK293 cells (8). To elucidate the biological functions of TMEM16 moonlighting, there is an urgent need to have an in-depth understanding of TMEM16 evolution and function in different kingdoms ranging from Protozoa and Fungi to Animalia.…”
mentioning
confidence: 99%